Development of Hockey Dribbling Exercises Android App-Based - Selly purnama; Ida Wahidah; Imam Badru Zaman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The objectives of this study are as follows: 1) To produce an android-based dribbling hockey practice application that is developed, 2) To determine the feasibility of an android application-based dribbling practice product that is being developed. The research method used is a research and development (R&D) approach. The results of this study were 1) successful design of an Android-based dribbling hockey practice application, 2) The results of the feasibility validity of dribbling hockey practice obtained percentages of 83%, 87%, and 86%, which means that the application developed is valid and feasible to use, 3) Based the SUS Score result is 73.42  which is in the good category so that overall the application made is feasible to use and effective for dribbling hockey practice based on user ratings.